Automated testing approach for corrad (web application framework) - Ismail, Mohd Faisal Imran (2015)
Every software development group tests their products, yet delivered software is not 100% free defects. Test engineers strive to catch them before the product is released but they always creep in and they often reappear, even with the best manual testing processes. In most cases, testing has to be done repeatedly throughout the development cycles to ensure quality. Manually repeating these tests is costly and time consuming. The most plausible solution to overcome this problem is by using automated testing. Not only it increases the effectiveness, efficiency and coverage of the software testing, automated tests can also be run over and over again at no additional cost. Furthermore, automated testing is much faster than manual tests, which can reduce the time to run repetitive tests from days to hours. Given the suggestion about automated testing above, this research is proposed to apply the automated testing approach on a web application framework, and a framework named CORRAD is chosen as the pilot study platform. The research demonstrated the approach with an automated testing tool that is integrated as a plugin for CORRAD. Evaluation of this approach shows that the automated testing approach can increase the effectiveness and efficiency of the testing process. Therefore, this approach is expected to increase the quality of the products developed using CORRAD, and reduce the time and cost needed for the testing process. In addition, it is believed that the developed tool can be commercialized as an added value for CORRAD.